Design and development of a versatile robot gripper - Lim, Osel Shaofeng (2017)
Industrial pick-and-place applications often require a gripper that is capable of handling objects of varying shapes and sizes. Also, the gripper should have a simple mechanical design and control architecture for it to be a practical and cost effective choice to be introduced into production lines. The objective of this project is to design and develop a versatile robot gripper that is capable of pinching and encompassing different object geometries. Through the evaluation of background researches, it was decided that the gripper in this project will be an underactuated mechanical adaptive gripper. This gripper has fingers that are four-bar linkages, rotated by a worm gear drive system. The fabrication of the gripper prototype is done by 3D printing. The assembled gripper prototype is then put through a simulation to grasp common household objects that have cross-sections of standard industrial raw materials. From the test observations, the gripper prototype is able to adapt to the objects’ surface profiles and execute the pinch or encompassing grip appropriately. Hence, the developed gripper is concluded to be a versatile one. However, there are still areas of improvement that can be made to the current design and should be undertaken in future works.